ASPEK PSIKOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL 5 CM KARYA DONNY DHIRGANTORO - Astuti, Sariyah; Puspita, Dian (STKIP PGRI Bandar Lampung, 2019)
This study aims to find out and describe: (1) the structure of the text in the novel 5 CM by Donny Dhirgantoro, (2) the psychological conflict of figures based on the theory of Abraham H. Maslow's needs contained in the 5 CM novel by Donny Dhirgantoro, (3) the value of education the character contained in the 5 CM novel by Donny Dhirgantoro, (4) its relevance in learning literature in higher education. This research is a descriptive qualitative research. The research approach used is the psychology literature approach. Data collection techniques used are interview techniques and document analysis. Data validity in this study uses triangulation theory and data sources. The data analysis technique used in this study is an interactive model analysis technique. The results of this study include: (1) the form of literature, which is seen from intrinsic and extrinsic elements, (2) psychiatric conflicts of figures based on Abraham H. Maslow's theory can be seen from the needs namely physiological, security, love and belonging, price self, and self-actualization needs. (3) in the 5 CM novel by Donny Dhirgantoro ten values ​​of character education were found, including religious character, discipline, hard work, creativity, national spirit, love for the motherland, respect for achievement, social/environmental care, responsibility and friendliness / communicative. 4) 5 CM novels by Donny Dhirgantoro have relevance to literary learning, one of them is learning Literary Criticism, which is as teaching material in learning Literary Criticism in Higher Education.